A Critical Approach to the Foundations of Occupational Therapy: Contributions to an Alternative Occupational Therapy; [Apontamentos Críticos Aos Fundamentos Da Terapia Ocupacional: Contribuições Para Uma Terapia Ocupacional Outra] - Guajardo-Cordoba, A (Universidade Federal de Sao Carlos, 2023)
This essay addresses, from a critical perspective of the Global South, what has been called the foundations of occupational therapy. It argues that these so-called foundations rely on certain constitutive categories that form the basis of the construction of concepts, theories, and frameworks with which the discipline operates, including mainly the notion of occupational nature, the concept of the individual, among others. These categories that support what has been referred to as the foundations of our work primarily derive from the world-system in which scientific disciplines have been produced, including occupational therapy, and correspond to the rationality of the modern Western, North Eurocentric project. The purpose of this essay is to critically analyze and reflect upon the fundamental categories of occupational therapy from a critical position of the Global South, which will open up the possibility of producing an occupational therapy radically different from those of the modern Western world-system. We will refer to it as "alternative occupational therapy," which is based on a radical rupture from the central categories of the profession. As an introduction, we propose other categories that promote a historically situated, decolonized understanding of the discipline oriented towards recognition and a South-South praxis that fosters intercultural dialogues breaking away from the universalism, monotopism, and monoculturalism of occupational therapy. © 2023 Universidade Federal de Sao Carlos. All rights reserved.